2017
DOI: 10.1245/s10434-017-5933-0
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors Associated with Post-Mastectomy Immediate Reconstruction in a Contemporary Cohort of Breast Cancer Survivors

Abstract: Background Post-mastectomy reconstruction is a critical component of high-quality breast cancer care. Prior studies demonstrate socioeconomic disparity in receipt of reconstruction. Our objective was to evaluate trends in receipt of immediate reconstruction and examine socio-economic factors associated with reconstruction in a contemporary cohort. Methods Using the National Cancer Database, we identified women < 75 years of age with stage 0-1 breast cancer treated with mastectomy (n=297,121). Trends in immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 27 publications
1
25
0
3
Order By: Relevance
“…Seniai įrodyta, jog krūties atstatymas yra tiesiogiai susijęs su geresne moters gyvenimo kokybe, apimant geresnę seksualinę, psichosocialinę bei fizinę jos funkciją. Tai taipogi yra krūties vėžio gydymo kokybės rodiklis [3]. Krūtį atstatančių operacijų skaičius JAV per 15 metų išaugo nuo 11,6% (1998 m.) iki 48% (2013 m.).…”
Section: įVadasunclassified
See 2 more Smart Citations
“…Seniai įrodyta, jog krūties atstatymas yra tiesiogiai susijęs su geresne moters gyvenimo kokybe, apimant geresnę seksualinę, psichosocialinę bei fizinę jos funkciją. Tai taipogi yra krūties vėžio gydymo kokybės rodiklis [3]. Krūtį atstatančių operacijų skaičius JAV per 15 metų išaugo nuo 11,6% (1998 m.) iki 48% (2013 m.).…”
Section: įVadasunclassified
“…Moterų, kurioms buvo galima atlikti krūtį tausojančias operacijas, vietoje jos pasirinkusių mastektomijas, skaičius išaugo nuo 34,3% (1998 m.) iki 37,8% (2011 m.). Taip pat abipusę mastektomiją esant vienos krūties onkologiniam susirgimui 2011 m. pasirinko 11,2% moterų, kai 1998 m. tokių moterų buvo tik 1,9% [3,4]. Egzistuoja keletas teorijų tokiam radikaliam moterų pasirinkimui paaiškinti.…”
Section: įVadasunclassified
See 1 more Smart Citation
“…Known contributing factors in the choice of IBR versus DBR versus no reconstruction are tumour characteristics, expected oncological treatment, surgical competence and resources, patient co‐morbidity and body habitus, and patient preference. Moreover, retrospective cohort studies have shown that non‐white ethnicity, lower education, older age and single status decrease the likelihood of having IBR. In a Danish study, the rate of IBR was significantly higher among women with higher education and in hospitals with plastic surgery departments.…”
Section: Introductionmentioning
confidence: 99%
“…26 Further, lower SES has been linked with a lower probability to undergo breast-conserving therapy or immediate breast reconstruction. 27,29 Yet, the impact of SES on psychological functioning and perceived satisfaction in survivorship has yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%